2014
DOI: 10.1186/1743-422x-11-184
|View full text |Cite
|
Sign up to set email alerts
|

Serologic screenings for H7N9 from three sources among high-risk groups in the early stage of H7N9 circulation in Guangdong Province, China

Abstract: BackgroundThe aim of this study was to assess the prevalence of the novel avian influenza A virus (H7N9) in three high risk groups. The groups were divided into those exposed through infected individuals, those exposed through poultry and those individuals exposed through the external environment, in the early stage of the epidemic in Guangdong Province, which is located in the southern region of China.MethodsSerologic studies were conducted among samples collected from individuals who had close contact with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
1
4
1
Order By: Relevance
“…Our study also found that among close contacts of infected patients, although several had an elevated HI titer, MN confirmation showed no evidence of infection; this is consistent with the results of a serologic study conducted in Guangdong in July 2013, which included close contacts12.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study also found that among close contacts of infected patients, although several had an elevated HI titer, MN confirmation showed no evidence of infection; this is consistent with the results of a serologic study conducted in Guangdong in July 2013, which included close contacts12.…”
Section: Discussionsupporting
confidence: 90%
“…Another in Guangzhou found 1.6% poultry workers with HI titers ≥40 14 , and a study in Zhejiang Province reported 6.3% poultry workers with HI titers ≥807. Although our study found a lower seropositive rate among poultry workers in Guangdong than prior studies conducted in this province12, 13, 14, our study showed a higher seroprevalence among poultry workers in Guangdong compared with the poultry workers from the other five provinces included in the study. Indeed, both of the two poultry workers with positive H7N9 neutralization antibodies in this study were from Guangdong.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Along with severe and fatal cases of H7N9 virus infection reported thus far 3 4 9 , mild and asymptomatic infections in humans were also observed by surveillance 3 10 11 12 and serological studies 13 14 15 16 . While few serological studies showed that higher seroprevalence of antibody against H7N9 virus was observed among poultry workers, compared with the general population, the results varied significantly by study 13 14 15 .…”
mentioning
confidence: 66%
“…After the virus shedding period, serologic assays are performed to detect virus specific antibodies [10,11].…”
Section: Introductionmentioning
confidence: 99%